Islamic Law, Collective Obligations and Pursuing a Just Global Order - Fadel, Mohammad (Universitas Islam Internasional Indonesia, 2024)
This paper explores the intersections of Islamic law, collective obligations, and the pursuit of global justice in the context of capitalism-induced instability. The author argues that the contemporary global order is marked by a state of “abnormality” due to capitalism’s dynamic nature of “creative destruction,” rendering traditional Islamic jurisprudence (fiqh) inadequate for addressing modern challenges. Instead, the concept of collective obligations (furūḍ kifāya) in Islamic law offers a promising framework for managing these crises. This paper examines the potential for Islamic legal principles to confront global issues such as inequality and poverty, emphasizing the necessity of reflexive, adaptive jurisprudence grounded in democratic governance and public good. By reimagining Islamic law to focus on collective welfare and institutional reform, Muslim-majority states could play a pivotal role in fostering a more just global order. The paper concludes by stressing the urgent need for political will and collaborative action, informed by Islamic values, to address the systemic inequalities perpetuated by the capitalist global order.